A Factor Analysis of Work Passion Characteristics of New Generation Personnel in Digital Content Industry - Kaewsomboon, Jantrarat; Cruthaka, Chomsupak; Yamsang, Woranuch; Chancharoen, Duangduen (Rajapark Journal, 2024)
In this dissertation, the researcher examines (1) the factors of the work passion characteristics; analyzes (2) the factors of the work passion characteristics; and confirms (3) the factor analysis of the work passion characteristics of new generation personnel in the digital content industry. The technique of mixed-methods research was employed. In-depth interviews were conducted with 17 experts. The data obtained from the expert interviews were analyzed for content and used to construct a questionnaire. The questionnaire data were collected from a sample of 520 new-generation personnel using accidental sampling. Exploratory factor analysis and confirmatory factor analysis were performed. The results revealed that: 1) The factors of the commitment characteristics mobilizing the performance of the new generation personnel in the digital content industry consisted of three aspects: (1) organization; (2) work; and (3) relationship. 2) The factor analysis of the work-passion characteristics of the new generation personnel under study consisted of six aspects. (1) The relationship of personnel in the organization consisted (2) The organizational management consisted (3) Work commitment consisted (4) Work collaboration consisted (5) Being a part of the organization consisted and (6) Being accepted in work consisted 3) The confirmatory factor analysis the work passion characteristics of the new generation personnel in the digital content industry using the model of measurement for the work passion characteristics confirmed only five aspects. These aspects were the relationship of personnel in the organization; organizational management; work commitment; work collaboration; and being accepted in work. The congruence of the model and the empirical data following the criteria which could be considered from the criteria of Chi-square/df = 4.127; CFI = .906; TLI = .904; RMSEA = .078; and RMR = .038.